2002
DOI: 10.1152/physiolgenomics.00062.2002
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II is associated with activation of NF-κB-mediated genes and downregulation of PPARs

Abstract: Angiotensin II (ANG II) promotes vascular inflammation through nuclear factor-kappaB (NF-kappaB)-mediated induction of pro-inflammatory genes. The role of peroxisome proliferator-activated receptors (PPARs) in modulating vascular inflammation and atherosclerosis in vivo is unclear. The aim of the present study was to examine the effects of ANG II on PPARs and NF-kappaB-dependent pro-inflammatory genes in the vascular wall in an in vivo model of atherosclerosis and aneurysm formation. Six-month-old male apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
174
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(184 citation statements)
references
References 37 publications
8
174
0
2
Order By: Relevance
“…Angiotensin II (AGII) has been shown to exert effects on both inflammation and oxidative stress via the AGII receptor subtype 1 [31,32]. In the current study we demonstrated a reduction in Agtr1 gene expression in the aortae of both control (p<0.05) and diabetic mice (p<0.05) with gemfibrozil treatment ( Table 2).…”
Section: Renin-angiotensin Systemsupporting
confidence: 59%
“…Angiotensin II (AGII) has been shown to exert effects on both inflammation and oxidative stress via the AGII receptor subtype 1 [31,32]. In the current study we demonstrated a reduction in Agtr1 gene expression in the aortae of both control (p<0.05) and diabetic mice (p<0.05) with gemfibrozil treatment ( Table 2).…”
Section: Renin-angiotensin Systemsupporting
confidence: 59%
“…The increased production of angiotensinogen by the adipose tissue is associated with high blood pressure and angiogenesis, both related to endothelial dysfunction. Similarly, the angiotensin II acts in the formation of oxygen-derived free radicals, decreasing the availability of nitric oxide and causing damages to the vascular tissue 31 .…”
Section: Angiotensinogenmentioning
confidence: 99%
“…16,17 Further, pretreatment of endothelial cells with anti-oxidants attenuates Ang II-and oxLDL-induced LOX-1 expression, 16,17 implying a common oxidant signaling pathway. As such, it appears that Ang II may activate LOX-1 promoter through the same mechanism as oxLDL.…”
Section: Analysis Of Ang Ii-induced Lox-1 Promoter Activationmentioning
confidence: 99%
“…The activation of NF-B p50 subunit in response to Ang II in endothelial cells is controversial. Some investigators 20,21 have shown the activation of both p50 and p65 subunits by Ang II, whereas others 16,22 showed the activation of only NF-B p65 by Ang II. We performed EMSA-supershift assay with antibody against NF-B p50 subunit, and found that Ang IIinduced shifted band was somewhat attenuated by the NF-B p50 antibody (data not shown).…”
Section: The Critical Role Of Nf-b In Ang Ii-induced Lox-1 Promoter Amentioning
confidence: 99%